Genetic Characteristics of Periophthalmus chrysospilos through COI Gene Analysis in Coastal Provinces of the Mekong Delta - Nguyen, Ton Huu Duc; Phan, Gieo Hoang; Dinh, Quang Minh (Trends in Sciences, 2025)
Periophthalmus chrysospilos is an amphibious gobiid species inhabiting intertidal mudflats and mangrove ecosystems across Southeast Asia, with the Mekong Delta as a critical habitat. This study investigates the genetic diversity of P. chrysospilos populations across 4 coastal provinces of the Mekong Delta - Tra Vinh, Soc Trang, Bac Lieu, and Ca Mau - through mitochondrial cytochrome c oxidase subunit I (COI) gene sequence analysis. Genomic DNA was extracted, amplified, and sequenced to assess nucleotide composition, genetic distances, and phylogenetic relationships. The analyzed COI gene sequences were 645 base pairs in length. The results demonstrated a high degree of sequence similarity (99.21 - 99.84 %) between P. chrysospilos populations in the Mekong Delta and those from Singapore. Nucleotide composition analysis revealed a higher proportion of adenine-thymine (AT) content than guanine-cytosine (GC). Furthermore, genetic distances among samples were minimal (0.00 - 0.03), suggesting low levels of genetic differentiation. Phylogenetic analysis clustered all sampled individuals into a single clade, confirming their classification as a single species. These findings indicate limited genetic divergence among populations and highlight the necessity for further investigations into environmental and anthropogenic factors affecting genetic structure. This study contributes to understanding P. chrysospilos genetic diversity and provides insights relevant to conservation and aquaculture management strategies. HIGHLIGHTS Effect of different explant fragmentation and different concentrations of 2,4 Dichlorophenoxyacetic acid (2,4-D) on callus induction of mihanovichii LB2178 Agua Dulce. Quantification of anthocyanins from callus of mihanovichii LB2178 Agua Dulce. Genetic stability of the mihanovichii LB2178 Agua Dulce using SSR markers. GRAPHICAL ABSTRACT